مدى استخدام المدربين للتخطيط العلمي لرفع مستوى منافسات ألعاب القوى - بجبوج, فؤاد (Latakia University Journal -Medical Sciences Series, 2018)
The main objective of this study is to define the way the trainers use scientific planning in order to raise the level of athletics. For this purpose , a special survey has been designed for specialists and experts. This study included 45 trainers who have followed special high level sessions , and it concluded that , there was a weakness in the use of scientific planning .However , it is the result of the lack of having the needed help of specialists , and being not able to use the technology of sport training , and using the classical means of measurement away from the objective diagnosis to achieve the aim of their already decided plans. Nevertheless , there is no continual following and estimating process by the people concerned , and recommends the researcher to find the appropriate solutions to all the problems that facing the trainers in order to raise the level of athletics competitions. هدفت الدراسة إلى التعرف على مدى استخدام المدربين للتخطيط العلمي من أجل رفع مستوى منافسات ألعاب القوى، ولهذا الغرض تم تصميم استبيان وترشيحه على الخبراء والمختصين، وتكونت عينة البحث من 45 مدربا ممن اتبعوا دورات تدريبية عالية المستوى، وتوصلت الدراسة إلى وجود ضعف في استخدام التخطيط العلمي لدى المدربين , وذلك نتيجة عدم الاستعانة بالخبراء والمختصين، وعدم استخدام تقنيات التدريب الحديث، واستخدام وسائل قياس تقليدية لتحقيق أهداف الخطط الموضوعة بعيدا عن التشخيص الموضوعي، مع عدم وجود خطط طويلة المدى لتحقيق مستويات رياضية عالية، ووجود مشكلات مادية ومعلوماتية وفنية وإدارية تواجه مدربي ألعاب القوى في عمليات التخطيط، إضافة إلى عدم المتابعة والتقويم للخطط التدريبية من قبل المعنيين بذلك؛ ويوصي الباحث بإيجاد الحلول المناسبة لكافة المشكلات التي تواجه المدربين من أجل رفع منافسات ألعاب القوى.